ANALISIS PERBANDINGAN POWER TRANSMIT PADA JARINGAN 3G TERHADAP KUALITAS EC/NO DAN RECEIVED SIGNAL CODE POWER DALAM HUBUNGAN INTENSITAS TRAFIK - ., Teguh Handarbeni (Faculty of Engineering, Universitas Tanjungpura, 2014)
In WCDMA cellular systems, the transmit power setting will affect the capacity and coverage of the area. The use of a small transmit power with a large amount of user can cause excess load on the network itself. so it is necessary to increase the transmit of power parameters. This study analyzed the ratio of the transmit power on the quality of Ec / No and RSCP in traffic intensity. results in Jalan Imam Bonjol (site 140 744) pontianak. This study shows that for best results of RSCP plot using 448 dBm power sector with a range of 2 -74 dBm to 0 dBm, the worst results using 430 dBm power sector with a range of -83 dBm 3 to -78 dBm and to plot the results of Ec / No , the best results use a transmit power range of 430 dBm to -4 dBm to 0 dBm, the worst results using 448 dBm transmit power with a range of -9 dBm to -12 dBm. For the calculation of the intensity of traffic, the highest value were obtained with 430 dBm transmit power at sector 3 which is got 1.6 at the result. The lowest traffic intensity obtained from 448 dBm transmit power in sector 2 which is got 0.05. From these results, we can take some good summaries that the transmit power changes have a major impact on the Received Signal Code Power (RSCP) and does not affect the quality of chips per Noise Energy as Ec / No is strongly influenced by the number of users. Related with the traffic intensity, changing the transmit power did not affect voice traffic intensity values ?significantly, since voice system redirected over 2G networks in principal of the system. Kata kunci - Power transmit, Recived Signal Code Power (RSCP), Energy Chip per Noise (Ec/No), Intensitas Trafik